Comprehensive In silico Analysis of Antibacterial Compounds in n-Hexane Fraction from Jeruju Leaf (Acanthus ilicifolius) - Wardani, Arief Kusuma; Haresmita, Perdana Priya; Alda, Mahkota; Vaira, Tischa (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2024)
In an emergency, to identify the most promising Hesperidin, Kaempferol-3,4'-di-O-methyl ether (Ermanin); Myricetin-3-glucoside, Peonidine 3-(4’-arabinosylglucoside); Quercetin 3-(2G-rhamnosylrutinoside); and Rhamnetin 3-mannosyl-(1–2)-alloside as a lead compound from Jeruju to develop new drugs from flavonoid analog. The active compound's structure is derived from the PubChem database and improves the stability through ChemDraw v19. The Protein Data Bank website identified the protein macromolecule with PDB code 3VSL. Redocking was performed to ensure validation of 3VSL. The docking method was carried out using the IGEMDOCK software version v2.1. Also, the chimera-1.13.1 program is used to know the interaction profile. The web server pkCSM and Protox II online tool were used to determine the toxicity. 3,7,11,15-tetramethyl-2-hexadecen-1-ol is the juju leaf chemical with the most promise as an antibacterial and the one that shows the maximum binding affinity when taking into account toxicity.